Mini meadows : grow a little patch of colorful flowers anywhere around your yard - Lizotte, Mike (North Adams, MA : Storey Publishing, 2019)
"Small space, big impact. Growing a patch of meadow plants is an easy inexpensive way to start your first garden. It's also an eco-friendly alternative to a lawn and can help prevent erosion and provide food for pollinators. Mike Lizotte guides you through the steps of choosing the perfeect plants for your space, prepping the ground for growing from seed, and enjoying your mini meadow for years to come."--
Meadow planning 101 -- Digging in -- Autumn and beyond -- Meadows with a purpose -- Planting for pollinators.
Includes index.
107419
Keywords: Flower gardening; Meadow gardening; Eco-friendly gardening